A numerical and experimental analysis of multi-hole orifice in turbulent flow. (April 2022) - Golijanek-Jędrzejczyk, Anna; Mrowiec, Andrzej; Kleszcz, Sławosz; Hanus, Robert; Zych, Marcin; Jaszczur, Marek
Highlights: Research on a prototype 4-hole orifice with module m = 0.25. CFD modeling for two turbulence models: k - ε -realizable and k -ω- BSL . A high accuracy numerical model was developed for Re = 4200–19, 000. The experimental results for volumetric flows in range 0.167–0.686 dm 3 /s. Numerical simulations for multihole orifice flowmeter. The experimental research was found to be very compatible with simulations. Abstract: In this research study, the comprehensive metrological analysis is investigated for a 4-hole orifice with module m = 0.25 installed in the pipeline with an internal diameter of 50 mm. A detailed numerical simulation was performed for the turbulence models: k-ε-realizable and k- ω -BSL . The novelties of the research include model validation by comparing the results of numerical studies with the experiment conducted in the area of developing turbulent flow in the range of Reynolds numbers from 4, 200 to 19, 000. Such validated models are sought by the system designers and can be used for further analyses and optimisation of this orifice in this flow type. The multi-hole orifices are less sensitive to flow disturbances than the standardized standard centric orifice. In addition, orifices of this type can be mounted in installations with much shorter sections upstream and downstream of the orifice - which is very often the case in industrial flow installations.